Assessment of referral system in health care delivery center of Paeengatab, Babol, 2003 - SR Hosseini (Babol University of Medical Sciences, 2005)
Background and objective: Since equal distribution of health services is impossible in different levels of health network, small centers should refer patients to upper level for special services and if it doesn’t be according to referral system, causes crowding and insufficiency of health services in upper levels and leads to uselessness of medical services in small centers. This study was done to assess the function of referral system in Babol health care delivery network. Methods: This cross-sectional study was performed in Paeengatab health center during autumn 2003. All referred patients to upper levels were included in this study. Data was collected by interviewing with patients and referral forms and then were analyzed. Findings: From 445 forms, 200 had complete data. Most referred patients were female (73%) and were at the age of 20-29 (42%). Most people (58.2%) were referred for paraclinical services (Sonography and laboratory) and the most referred cases were the patients with gynecological and obstetric disorders (18.6%). Shahid Beheshti, Yahyanejad and Amirkola hospitals accepted the most referred patients, respectively. The feedback rate from hospital to health centers was zero. Conclusion: Referral system is only being performed as one way from health centers to hospitals and there is no feedback, since, gynecological and obstetric disorders make the largest number of referred patients, it is necessary to increase health and treatment services in rural health centers in order to decrease the number of patients who referred to hospitals.